Peningkatan Ketebalan Serat Elastin Dinding Vagina pada Prolapsus Organ Pelvis Anterior - Achmad Zaki; Eighty Mardian; Sjahjenny Mustokoweni (Universitas Airlangga, 2016)
Objectives: To measure the thickness of elastin fibres on vaginal wall of patients with POP anterior and then analyse the correlation of this measurement with the degree of POP anterior.Materials and Methods: This research is an observational analytic study. Data collection was conducted with a cross sectional approach on 28 blocks paraffin of vaginal wall taken from POP anterior patients of whom went through an operation in Dr. Soetomo Hospital of Surabaya. Data was divided into four groups: degree 0/I , II, III and IV respectively (n = 7). Immunohistochemical staining was performed with antibodies elastin. Afterward, the thickness of the elastin fibres was measured by utilizing a microscope with a Leica Application Suite (LAS) software.Results: We found significant differences in the mean of thickness of elastin fibres in each group of patients with degrees of anterior POP 0/I , II , III and IV respectively 0,81 + 0,14 µm; 1,63 + 0,19 µm; 2,47 + 0,26µm and 3,19 + 0,36 µm (p < 0,0001 ). Based on Pearson correlation test, the results shows a correlation coefficient r = 0.965 (p < 0,0001).Conclusion: The thickness of elastin fibre on vaginal wall increased as the degree of POP anterior arise. Increased in the thickness of elastin fibers on the vaginal walls was the result from extracellular matriks remodelling on vaginal wall of anterior POP patient.